Neuro-Linguistic Programming as a Teaching Method to Enhance the Foreign Language Teaching ("Conference on Universal Science Research 2023", 2023)
Foreign language educators employ a variety of techniques and resources to facilitate effective communication with their students. Recent advancements in the field of language instruction, particularly in the realm of Neuro-Linguistic Programming (NLP), have greatly contributed to our understanding of the communicative aspects of foreign language teaching and learning.This paper delves into the integration of Neuro-Linguistic Programming (NLP) within the classroom environment to enhance educators' communication skills with their students. The primary focus of this study lies in the utilization of Neuro-Linguistic Programming (NLP) for foreign language acquisition, aiming to identify shortcomings and challenges associated with traditional language learning methods.The adoption of Neuro-Linguistic Programming (NLP) in Foreign Language (FL) education holds significant promise, as it has demonstrated its effectiveness through the substantial progress witnessed in numerous countries where it has been applied. The paper defines the term Neuro-Linguistic Programming and it deals with its usage as an educational strategy for second language teachers.